81.9k views
11 votes
Factorize 4x2-5x-6 Please help with this question

User Lofcek
by
6.1k points

2 Answers

5 votes

Answer:

(x - 2)(4x + 3)

Explanation:

4x² - 5x - 6

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 4 × - 6 = - 24 and sum = - 5

The factors are - 8 and + 3

Use these factors to split the x- term

4x² - 8x + 3x - 6 ( factor first/second and third/fourth terms )

= 4x(x - 2) + 3(x - 2) ← factor out (x - 2) from each term

= (x - 2)(4x + 3) ← in factored form

User Lutti Coelho
by
4.9k points
13 votes

Answer: Let us write down the equation and try to find one of the factors.

4x^2 + 5x - 6 = 0

4x^2 + 8x - 3x - 6 = 0

4x(x + 2) - 3(x + 2) = 0

(4x - 3)(x + 2) = 0

From the above deduction we can easily conclude that one of the factors of the equation given in the question is (4x - 3). The correct option among all the options that are given in the question is the fourth option or option "D

User Pandurang Waghulde
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.